Exercise and growth hormone: does one affect the other? - Roemmich, J. N.; Rogol, A. D. (The Journal of Pediatrics, 1997)
The release of growth hormone (GH) is sensitive to many pharmacologic and physiologic stimuli, including exercise. Although the role of the increased amount of GH released during exercise is not fully understood, it most likely contributes to metabolic fuel adaptations during exercise, and tissue repair after the exercise session. The GH response to exercise is altered by many factors, including sex steroid concentrations, fitness level, and the intensity of previous exercise sessions. For both endurance and resistance exercise, greater activation of anaerobic glycolysis and lactate formation increases the amount of GH released. Whether an endurance exercise session or an endurance exercise training regimen influences the total amount of GH released during a 24-hour period is not clear; this may depend on the gender of the person, the intensity of the exercise, and the duration of exercise training. The influence of a single session of resistance exercise or resistance training on 24-hour GH secretion has not been studied. Preexercise diet modulation (especially modulation of fat intake) may also influence the release of GH during endurance exercise. Studies that measure the 12- to 24-hour GH response to resistance exercise after the ingestion of various macronutrient diets have not been completed.